O problema da sociabilidade em Jean-Jacques Rousseau - Rodrigues Junior, Edward Pereira (2008)
The goal of this work is to reflect about the sociability problem in Jean-Jacques Rousseau. For the jurisconsults of school of the natural right, as well as for Locke, the sociability is a characteristic trace of the human nature. Thus, it can understand easily that, being the naturally sociable man, he stipulates without difficulty the organization of the political body, when this seems to you convenient. In Hobbes, the situation is different, because the civil society is resultant of the peace and safety wish and particularly of the fear of the violent death in a war state in which the human company expresses through an innate belligerent and natural inclination. Rousseau, as well as Hobbes, denies the natural sociability, but on the other side of the author of Leviathan, considers that, in the state of original nature, the man lives in the more complete loneliness and independence, once, when not finding in your absolutely impassable middle obstacles, it satisfies fully their needs, because these are simple and of order purely physical and biological. In this perfect balance state between wishes and needs, the natural man, only led by the instinct, does feel need to their fellow creatures help, until new circumstances modify the balance of your environment, awaking him new needs. Inclusively, they are these new needs that provoke the union among men. In this idea, however, there is something of generous for with human nature, because to when admitting the possibility of benefit us of our union, Rousseau affirms that the man is by nature good, and that is possible to cohabit under the auspices of this natural kindness